Respuesta :
Answer:
The correct option is 2.
Step-by-step explanation:
The given function is
[tex]f(x)=x^4+5x^3-4x^2-8x+6[/tex]
If (x-c) is a factor of a function, then f(c)=0.
In option 1:
[tex](2x+3)=0[/tex]
[tex]x=-\frac{3}{2}[/tex]
[tex]f(-\frac{3}{2})=(-\frac{3}{2})^4+5(-\frac{3}{2})^3-4(-\frac{3}{2})^2-8(-\frac{3}{2})+6=\frac{-45}{16}\neq 0[/tex]
Therefore option 1 is incorrect.
In option 2:
[tex]x-1=0\Rightarrow x=1[/tex]
[tex]f(1)=(1)^4+5(1)^3-4(1)^2-8(1)+6=0[/tex]
Therefore option 2 is correct and (x-1) is a factor of f(x).
In option 3:
[tex](2x-3)=0[/tex]
[tex]x=\frac{3}{2}[/tex]
[tex]f(\frac{3}{2})=(\frac{3}{2})^4+5(\frac{3}{2})^3-4(\frac{3}{2})^2-8(\frac{3}{2})+6=\frac{111}{16}\neq 0[/tex]
Therefore option 3 is incorrect.
In option 4:
[tex]x+1=0\Rightarrow x=-1[/tex]
[tex]f(-)=(-1)^4+5(-1)^3-4(-1)^2-8(-1)+6=6\neq 0[/tex]
Therefore option 4 is incorrect.